The effect of spatial boundaries on memory in a virtual environment. - Lamont, Julie C.; Bilkey, David K. (Memory & Cognition, 2026)
Crossing a spatial boundary, such as a doorway, often signals the ending of one episode and the beginning of another, segmenting ongoing experience into events. When conducted in real environments, this 'doorway effect' differentially affects memory for objects encountered within and between events. The evidence for this occurring in immersive virtual reality (VR) environments is mixed. The present study investigated the 'doorway effect' in a VR environment and also examined how event memory is affected when segmentation processes are disrupted by interference tasks. Ninety participants explored a five-room VR building containing interactable objects. During exploration, some participants were presented with virtual distractor tasks that required either visuospatial working memory or simple rapid-reaction responses. These tasks occurred either at doorways or in the middle of rooms. Later recall for the temporal order and contextual location of objects was examined and compared with controls, who explored the building without any distractions. The results showed that a doorway effect was evident in the control, no-distractor condition. The visuospatial distractor task impaired memory for objects, but only when it occurred in the middle of a room, possibly because it separated the representation of the encapsulating room into different events. When this task was performed in the doorway, however, its effects overlapped with, and did not add to, the spatial boundary effect. Together these findings show that both spatial boundaries and spatial distractor tasks can segment memory for experience in an immersive VR environment.